2015
DOI: 10.1063/1.4913586
|View full text |Cite
|
Sign up to set email alerts
|

Order within disorder: The atomic structure of ion-beam sputtered amorphous tantala (a-Ta2O5)

Abstract: Amorphous tantala (a-Ta2O5) is a technologically important material often used in high-performance coatings. Understanding this material at the atomic level provides a way to further improve performance. This work details extended X-ray absorption fine structure measurements of a-Ta2O5 coatings, where high-quality experimental data and theoretical fits have allowed a detailed interpretation of the nearest-neighbor distributions. It was found that the tantalum atom is surrounded by four shells of atoms in seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…Extended X-ray Absorption Fine Structure (EXAFS) shows more extensive order to perhaps the 3rd or 4th nearest neighbour and is chemically sensitive to the ordering about specific atoms, although this still does not reveal any order beyond 1 nm. Our recent work has shown that this provides further insights into the behaviour on annealing [15]. The previous electron diffraction studies have shown the atomic structure to be homogeneous at volumes probed with electron beams of 50 nm in lateral extent up to a 600°C heat treatment, whereas in the present study the atomic structure is shown to be heterogeneous over volumes probed with an electron beam of 2 nm in lateral extent.…”
Section: Introductionsupporting
confidence: 53%
“…Extended X-ray Absorption Fine Structure (EXAFS) shows more extensive order to perhaps the 3rd or 4th nearest neighbour and is chemically sensitive to the ordering about specific atoms, although this still does not reveal any order beyond 1 nm. Our recent work has shown that this provides further insights into the behaviour on annealing [15]. The previous electron diffraction studies have shown the atomic structure to be homogeneous at volumes probed with electron beams of 50 nm in lateral extent up to a 600°C heat treatment, whereas in the present study the atomic structure is shown to be heterogeneous over volumes probed with an electron beam of 2 nm in lateral extent.…”
Section: Introductionsupporting
confidence: 53%
“…Recently published Ta-centered local structure from Ta L 3 edge EXAFS data3031 indicate that the Ta ions are surrounded by between 5 and 6 oxygens. There are different ways in which these Ta centered polyhedra connect to each other to give rise to different polymorphs.…”
Section: Resultsmentioning
confidence: 99%
“…Extracting the bond distances and average coordination number constrains (shown in Fig. 2b), from Ta-centered information from Ta L 3 edge EXAFS data3031 and O-centered information from NMR spectroscopy32, we construct the backbone of the topological PSU as a kinked Ta-O-Ta chain, with a Ta-O bond of ca. 2.05 Å and a Ta-O-Ta angle of approximately 135–150 degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Techniques such as Extended X-ray Absorption Fine Structure (EXAFS) and Fluctuation Electron Microscopy (FEM) have recently been used to explore the atomic structure of tantala and Ti-doped tantala [97,98]. Theoretical modeling by using density functional theory molecular dynamic simulation with reverse Monte Carlo refinements [99,100] in conjunction with the experimental probing techniques will be useful to gain insight for the mechanical loss of the amorphous coating materials and will lead to feedbacks for material tailoring for improving coatings of the laser interference gravitational wave detector.…”
Section: Correlations Between Atomic Structure and Mechanical Lossmentioning
confidence: 99%